1996
DOI: 10.1038/hdy.1996.59
|View full text |Cite
|
Sign up to set email alerts
|

Empirical assessment of allozyme and RAPD variation in Pinus sylvestris (L.) using haploid tissue analysis

Abstract: We analysed 20 allozyme and 22 putative random amplified polymorphic DNA (RAPD) loci in two populations of Pinus sylvestris (L.) from northern Sweden. Genotypes for individual allozyme and RAPD loci were inferred from segregation patterns in haploid macrogametophytes. Therefore, it was possible to distinguish between homo-and heterozygotes carrying a RAPD fragment and to estimate directly the frequencies of RAPD fragments. The percentage of polymorphic loci and the expected and observed heterozygosity were low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
1
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(106 citation statements)
references
References 24 publications
6
97
1
1
Order By: Relevance
“…This is consistent with the majority of previous studies comparing these two population genetic markers (Table 2), though there are exceptions to this trend (Liu andFurnier, 1993, LeCorre et al, 1997;Ross et al, 1999). Mostly, this difference is explained by the inherently higher rate of detectable mutations and weaker degree of selective constraint at RAPD compared to allozyme loci since RAPDs can detect variation in both coding and noncoding regions (Szmidt et al, 1996;Aagaard et al, 1998;Waycott, 1998;Sun et al, 1999;Wu et al, 1999;Oiki et al, 2001).…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with the majority of previous studies comparing these two population genetic markers (Table 2), though there are exceptions to this trend (Liu andFurnier, 1993, LeCorre et al, 1997;Ross et al, 1999). Mostly, this difference is explained by the inherently higher rate of detectable mutations and weaker degree of selective constraint at RAPD compared to allozyme loci since RAPDs can detect variation in both coding and noncoding regions (Szmidt et al, 1996;Aagaard et al, 1998;Waycott, 1998;Sun et al, 1999;Wu et al, 1999;Oiki et al, 2001).…”
Section: Discussionsupporting
confidence: 90%
“…Use of RAPD markers for the parentage analysis has been limited (Welsh et al 1991, Scott et al 1992, Akerman et al 1995, because of their dominant character. However, the limitation of the dominant nature of RAPD markers can be alleviated by the segregation analysis of haploid megagametophytes (Lu et al 1995, Szmidt et al 1996. We were able to identify the male parents of most seedlings from the diagnostic progeny, by comparing the genotype of orchard clones inferred by analyzing Fig.…”
Section: Discussionmentioning
confidence: 99%
“…No geographic trends could be revealed for the ribosomal DNA variation (Karvonen and Savolainen 1993). Szmidt et al (1996) reported no RAPD variation between two Swedish Pinus sylvestris populations from latitudes 64° and 67°, respectively. Owing to the high variability in some of the DNA markers as well as their presumed neutrality they are excellent tools for studies on gene flow.…”
Section: Isozymesmentioning
confidence: 93%